Hopelessness and youth violent behavior: a longitudinal study - Demetropoulos Valencia, Janie (Deviant behavior, 2021)
Researchers have often neglected the role of hopelessness in violent behavior during adolescence. Moreover, little research has examined this relationship over time. Using data from Waves I and II of The National Longitudinal Study of Adolescent Health, we explore the relationship between hopelessness and youth violent behavior over time. Poisson regression was used to analyze contributors to violence in just Wave I, and again across time in Wave II using explanatory and control variables from Wave I. Results indicate that hopelessness is positively associated with violent behavior. Furthermore, while hopelessness and most other explanatory variables predicted violent behavior in Wave I, almost all variables became non-significant or negative except hopelessness and acts of minor delinquency when predicting violence in Wave II.